HOW DO YOU ASSESS YOURSELF - Djawa, Djibrael; Langi2, Cysca Adelaide Juliana; Maramis, Diana Roweina (MANAJEMEN ADMINISTRASI BISNIS DAN PEMASARAN, 2024)
This article aimed to explain how the role of the hotel manager as the Broker Role and Innovator Role in the open system model. Managers who act as brokers must have the ability to plan, and controlling, especially in the field of food and drinking and accommodation. Meanwhile, the role of an innovator is that a manager must be creative and innovative in implementing changes in oranization. Therefore, a manager needs to have the ability to negotiate and help employees to solve problems faced and challenge employees for the advancement of oranization in the future, and also act as a mediator